Mechanisms and Genetics of Resistance to Sodium Lauryl Sulfate in Strains of Shigella and Escherichia coli - Corwin, L. M. (1971)
The sensitivity to sodium lauryl sulfate (SLS) of Shigella flexneri and Escherichia coli is determined by at least three genes. One site is located near the lactose operon, and two loci are cotransducible with the arabinose operon. Calcium ions protect against SLS lysis. One gene is concerned with the relative ability of the bacterium to retain calcium against such chelating agents as ethylenediaminetetraacetic acid or phosphate buffer. This was first observed in a mutation from virulence to avirulence in S. flexneri with a concomitant loss of ability to penetrate the intestinal epithelium. The avirulent strain is far less sensitive to lysis by SLS in the presence of phosphate buffer than its virulent parent. The avirulent strain is also less sensitive to lysozyme and ethylenediaminetetraacetic acid. E. coli K-12 is much more sensitive to SLS than both of these Shigella strains. An E. coli-S. flexneri hybrid, which is unable to survive well in the gut and thus only produces an abortive infection, has inherited this extreme sensitivity to SLS.